The Effect of Board of Commissioners and Independent Commissioners on Agency Cost through Capital Structure - Wahidah, Siti Asroliatun; Ardiansari, Anindya (Universitas Negeri Semarang, 2019)
Different interests between managers and shareholders can emerge agency conflicts resulting agency costs. The aim of this study is to determine the effect of board of commissioners and independent commissioners to agency cost through capital structure. This study was conducted on companies incorporated in the LQ45 Index listed on the BEI 2012-2016. The number of samples based on purposive sampling method is 24 companies or 120 analysis units. Multiple regression analysis and path analysis using Eviews 9 were used for methods of data analysis. The results showed that board of commissioners have positive and insignificant effect on capital structure, while independent commissioners have positive and significant effect on capital structure. The capital structure has a negative and significant effect on the agency cost proxied by asset utilization ratio, board of commissioners has a negative and insignificant effect on the agency cost proxied by asset utilization ratio, whereas the independent commissioner has a positive and significant effect on the agency cost proxied by asset utilization ratio. By using path analysis, capital structure is unable to mediate the effect of board of commissioners and independent commissioners against agency cost.